Design routine and characterisation of a biconic deformable metal mirror for focus shifting - Boettner, Paul; Brady, Aoife; Reinlein, Claudia; Eberhardt, Ramona; Nolte, Stefan (Optics Express, 2021)
This paper describes an opto-mechanical concept of a deformable metal mirror membrane, which can shift the focus position over a large range by use of a single actuator. The core element of the mirror is a diamond turned tulip-shaped membrane, the design is optimized to correct astigmatic aberrations which arise from the use of a curved mirror under a deflection angle. For this purpose, the target mirror surface is biconic. The manufactured mirror was tested with a maximum central deflection of 28 μm and, when used in combination with a 200 mm focal lens, is capable of producing a focus shift of up to 17.9 mm with a resulting wavefront aberration of 238.7 nm RMSerror.
CRIS-Team Scopus Importer:2023-04-20